Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
On left: Chris Marie Brown, Luisa Medina and Patience Milrod; On right: ? Mendoza, Alice Mendoza, John Joyce and Virginia Salmeron